Fatigue behavior of square steel strut-to-gusset plate welded connections under eccentric compression: Full-scale and reduced-scale tests - Xu, Xiaoqing; Luo, Hongfa; Wang, Bin; Liu, Yuqing; Miao, Kaixiang; Hao, Rui; Lin, Weiwei; Zhou, Yuwen; He, Dongyang; Asadujjaman, Md (Engineering structures, 2025)
For a composite box girder bridge with cantilever deck slabs, its welded connection between external inclined strut and gusset plate is subject to combined axial force and bending moment. Considering heavy vehicles on the outside lane, the connection is the most unfavorable fatigue detail and of critical concern. Thus, one full-scale and two reduced-scale specimens to model the welded connection with 24 mm thick gusset plate and 20 mm thick strut wall were fabricated and tested, and the evolution of strain and fatigue crack was recorded. The specimens' fatigue lives were compared with existing experimental data and the design fatigue curve in the codes. The results showed that on the higher-loaded side of the connection, the welded detail suffering compressive stress cycles exhibited fatigue cracking, and the FAT45 curve in Eurocode 3 and IIW is generally conservative for fatigue life prediction. Specimens with steel plate thickness less than 10 mm in the literature and reduced-scale specimens in this study have a higher fatigue strength than the full-scale one, and thus, provide an overestimation of the actual connection's fatigue life, which confirmed the necessity of full-scale fatigue testing. Moreover, the residual tensile stress was found to be an important cause of fatigue crack propagation. •Welded connection with 24 mm thick gusset plate and 20 mm thick tube wall was studied.•Fatigue life and crack propagation mechanism under eccentric compression was revealed.•Reduced-scale tests provide an overestimation of the connection's fatigue life.